Red, White, and Boyle: Fiction as Propaganda and Art - Rai PETERSON (E-REA)
From the mid 1930s to the late 1950s, Boyle was mistakenly identified both as a Nazi and a Communist sympathizer. Many of her American critics misunderstood or oversimplified the complicated political world she knew and navigated deftly. When pressed by her own government to defend her loyalty to American democracy, she offered examples from her fiction as the final “proof” of her anti-Communist convictions. Exculpating herself from political charges imperiled, not just her career, but also the context for her writing itself. Still she rose above the challenge to produce good stories about taking responsibility to ensure her own freedoms.